The Live Universe. A Biologist's Perspective - Ferreira, Ricardo B.; Ferreira, João B. (Frontiers in Astronomy and Space Sciences, 2017)
Astrobiology looks at all aspects related to life in places other than the Earth, including its biomolecular building blocks and suitable environmental conditions. In the present article, a different approach is followed: a comparative analysis between Astronomy and Biology as discrete domains of science. Remarkable similarities exist between these two apparently widely separated and multidisciplinary fields. Both are driven, from beginning to end, by thermodynamics. Their evolution is studied to a very reasonable degree of accuracy, from beginning to the present day, by analyzing data which were ‘frozen’ in the past. Yet we cannot predict where and how they will go from here. A major difference is that in Biology, unlike Astronomy, we can see and analyse the present (or, more accurately, the immediate past). While the Big Bang is widely accepted as the origin of our universe, the debate about its ultimate fate is far from settled. A plethora of cosmological models has been proposed, many involving the concept of a multiuniverse. The observation that the rate of expansion of the universe is apparently accelerating further boosts the discussion. Entropy may act as a driving force behind the increasing rate of expansion, with nothingness as the maximum possible entropy our universe gets. Using biological systems as an analogy and adopting a broad definition for life, we may speculate the existence of a living multiuniverse, capable of natural evolution, in which each individual universe spontaneously goes through birth, development, reproduction, ageing and death. The possible roles of supermassive black holes (SMBHs) and human-like intelligence on the future evolution of our universe are briefly discussed.